Between-limb differences during 180° turns in female soccer players: application of statistical parametric mapping - Thomas, C.; Dos'Santos, T.; Warmenhoven, J.; Jones, P. A. (The Journal of Strength and Conditioning Research, 2022)
This study was exploratory in nature and investigated the ability of statistical parametric mapping (SPM) to assess between-limb differences in lower-extremity movement change of direction. Fourteen female soccer players (mean ± SD; age = 20.6 ± 0.6 years; height = 1.65 ± 0.07 m; and body mass = 56.04 ± 6.20 kg). For comparisons between preferred and nonpreferred limbs, vertical (Fz) and horizontal (Fx) ground reaction force were determined along with hip, knee, and ankle angles and moments in the sagittal plane during weight acceptance during the final contact. In addition, frontal plane knee abduction angles and moments were calculated during the final contact. Statistical parametric mapping software was then used to assess for differences between the entire weight acceptance phase of preferred and nonpreferred limbs. There were no differences between limbs in all variables using SPM. These results demonstrate that female soccer players exhibit little side-to-side differences in certain lower-limb biomechanics when performing a turn maneuver. These findings can be utilized by practitioners and clinicians when developing injury prevention and rehabilitation programs.